Neutrino masses through a type II seesaw mechanism at TeV scale - Montero, J. C.; Pires, CAD; Pleitez, V (Elsevier B.V., 2001)
In this work we show that we can generate neutrino masses through the type II seesaw mechanism working at TeV scale in the context of a 331 model. (C) 2001 Published by Elsevier B.V. B.V.